Reducing the environmental impact of surgery on a global scale: systematic review and co-prioritization with healthcare workers in 132 countries - National Institute for Health and Care Research Global Health Research Unit on Global Surgery; Adisa, A; Bahrami-Hessari, M; Bhangu, A; Singh, A (Oxford University Press, 2023)
Background: Healthcare cannot achieve net-zero carbon without addressing operating theatres. The aim of this study was to prioritize feasible interventions to reduce the environmental impact of operating theatres.